Effectivity Of Learning The Book Of Ta'lim Muta'allim In Forming Akhlakul Karimah Of Students In Madrasah Aliyah Nahdlatul Ulama Hasan Muchyi Kapurejo Pagu Kediri - Alfiah Nurcholidah; Ma’ma Mumajad; Suyono Suyono; Firnanda Erindia (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Morals are behavior that has become the habit of every individual which is seen in daily actions. Religious education in Islamic schools still maintains yellow learning to instill moral values ??based on spirituality for students. One of them is the book of ta'lim muta'allim as a support for the formation of students' morality. This study aims to find out how the learning and results of the ta;lim muta’allim book in shaping the akhlaqul karimah of students at the Madrasah Aliyah Nahdlatul Ulama Hasan Muchyi Kapurejo Pagu Kediri. This research uses a qualitative approach with case study. The data collection method uses observation and documentation methods. Meanwhile, data analysis was carried out by collecting data, reducing data, and drawing conclusions. Furthermore, to check the validity of the data, researchers used the triangulation method of sources and techniques. The results of the study show that the learning process of the muta'allim book of ta'lim, which includes the teacher selection system, learning methods, learning media used, student responses, teacher constraints and evaluation of learning and the results of learning the muta'allim book of ta'lim in forming akhlaqul karimah in the form of attitude of responsibility, tawadhu, discipline and ta'dzim along with the supporting factors.